Elongated Focus Optoacoustic Microscopy with Matched Bessel Beam Illumination and Ultrabroadband Axicon Detection. Issue 5 (28th January 2022) - Ali, Zakiullah; Zakian, Christian; Ntziachristos, Vasilis
Abstract : Current optoacoustic (OA) microscopy configurations often have narrow focal ranges that limit their use for fast volumetric imaging applications. Herein, the focal range of OA microscopes is extended by matching the elongated optical illumination profile of a Bessel beam with the pencil beam acoustic sensitivity profile of a broadband axicon detector. An inverted OA microscope is developed with interchangeable optical illumination and acoustic detection units to assess the working distance and resolutions retained with several combinations of illumination and detection profiles. Matching Bessel illumination with axicon detection extends the depth of focus 17‐fold over traditional configurations. Imaging a tilted mouse ear with the matched Bessel−axicon configuration reveals vasculature over a working distance exceeding 4.2 mm with optical resolution, while affording a sixfold increase in imaging volume over the same scanning duration compared with configurations using standard Gaussian illumination, demonstrating this approach's promise for increasing applications for OA microscopy in preclinical research. Abstract : Optoacoustic microscopes use Gaussian beam excitation with broadband spherically focused detection to obtain high‐resolution images; however, this combination limits imaging to a plane determined by the focal length of the Gaussian beam. To enable high‐resolution volumetric imaging, the elongated foci of Bessel beam illumination with the pencil beam sensitivity profile of a broadband axicon transducer are combined.